UNC569-induced Morphological Changes in Pigment Epithelia and Photoreceptor Cells in the Retina through MerTK Inhibition in Mice. (February 2018) - Sayama, Ayako; Okado, Keiko; Nakamura, Koichi; Kawaguchi, Tatsuya; Iguchi, Takuma; Makino, Toshihiko; Yabe, Koichi; Kai, Kiyonori; Mori, Kazuhiko
Mer proto-oncogene tyrosine kinase (MerTK), which is expressed in the retinal pigment epithelium (RPE), regulates phagocytosis of shed photoreceptor outer segments (POS). To investigate the effects of drug-induced MerTK inhibition on the retina, UNC569, a specific MerTK inhibitor, was orally administered to male mice at a concentration of 60, 100, or 150 mg/kg for up to 14 days. Furthermore, MerTK inhibition in the retinal tissue sample was examined using a phosphorylation assay following a single dose of UNC569 at 100 mg/kg. In electron microscopic examination, UNC569 at 100 mg/kg or more increased phagosomes and phagolysosomes in the RPE. In addition, UNC569 at 150 mg/kg increased chromatin-condensed nuclei in the outer nuclear layer, indicating the early phase of apoptosis of photoreceptor cells. MiR-183, miR-96, and miR-124, which are enriched in photoreceptor cells, were elevated in the plasma of mice following treatment of 150-mg/kg UNC569, in conjunction with the photoreceptor lesion. Additionally, 100-mg/kg UNC569 inhibited MerTK phosphorylation in the retina. These results suggest that MerTK inhibition impaired phagocytic function of the retina, leading to accumulation of shed POS within the POS layer and increasing phagosomes and phagolysosomes in the RPE to delay POS renewal, resulting in apoptosis of photoreceptor cells.